Toward a Renewed Cistercian Mysticism - Olivera, Bernardo (Cistercian studies quarterly, 2003)
Reports on the progress toward a renewed Cistercian mysticism. Mystical experience of Christian life; Fulfillment of the mystery of Jesus Christ in the Church; Distinction between mystical tradition and cistercian asceticism.